The measurement of maturity level of information technology service based on COBIT 5 framework - Lanto Ningrayati Amali; Muhammad Rifai Katili; Sitti Suhada; Lillyan Hadjaratie (Universitas Ahmad Dahlan, 2020)
Institutions are currently progressing on IT development and maximization in order to advance for good IT governance. Lack of comprehensive requirements analysis of IT utilization may lead to hindrances within IT development from achieving effective outcomes. This quantitative study employs control objective for information & related technology (COBIT 5) business framework to assess and identify the maturity level of IT service, primarily within the domain of delivery, service, and support (DSS). Data were obtained through questionnaire, observation, and documentation. The result reveals that the average maturity level of IT service is in level 3 (established); by which the study recommends for enhancements and upgrades in IT performance and service within the scope of compliance and IT service application and support.